TINGKAT SERANGAN ULAT KANTONG Metisa plana Walker (Lepidoptera: Psychidae) TERHADAP UMUR TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI KEBUN MATAPAO PT. SOCFIN INDONESIA - Nugraha Sembiring Nugraha Sembiring; Mena Uly Tarigan; Lisnawit Lisnawit (Universitas Sumatera Utara, 2013)
The attack rate of bagworms Metisa plana Walker (Lepidoptera: Psychidae) on the age of oil palm(Elaeis guineensis Jacq.) at Matapao Plantation, PT Socfin Indonesia. Under the supervision ofMena Uly Tarigan as the chairperson and Lisnawita as the member. The aim of the research was toknow the attack rate of bagworms (Metisa plana Walker) on the age of oil palm at the planting areaof TBM (pre-producing plant) and TM (post-producing plant). The research was conducted atMatapao Plantation, PT Socfin Indonesia, Teluk Mengkudu Subistrict, Serdang Bedagai Districtwith the altitude of ± 20 meters from the sea level. The research used a survey method withdiagonal samples. The results of the research showed that the attack rate of bagworms was higheron the TBM than on TM. The highest number of pests was found at block 27 in the planting year of2011 with 119 pests, while the highest rate of attack by bagworms (19.758%) was found at block 28in the planting year of 2009. The highest attack of bagworms was found in sample 50 at block 27 inthe planting year of 2011 with 15 pests in each frond. The highest intensity of bagworms’ attack(50%) was in sample 50 at block 27 in the planting year of 201, and it was categorized as amoderate attack.Keywords: bagworms Metisa plana, oil palm, the age of oil palm